EXPLORING FACTORS AFFECTING FRAUDULENT FINANCIAL REPORTING USING PENTAGON THEORY - Santoso, Kenny; Marlinah, Aan (Journal of Applied Finance and Accounting, 2024)
This research aims to prove empirical evidence of the influence of fraudulent financial reporting factors with the fraud pentagon model approach, such as Pressure (financial targets, financial stability, external pressure), Opportunity (ineffective monitoring, nature of industry), Rationality (the change of auditors), Capability (change of directors) and Arrogance (the number of CEO’s picture) on fraudulent financial reporting. The sample method of this study used purposive sampling method and produces 213 data or 71 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. The data has been obtained then analyzed using the multiple regression method.. The results of this study prove that external pressure and change of directors has effect on fraudulent financial reporting, while financial targets, financial stability, ineffective monitoring, nature of industry, the change of auditors (KAP), and the number of CEO’s picture have no influence on fraudulent financial reporting. The results of this study have implications for the theory of fraudulent financial reporting by investigating fraud indicators in CrowI's fraud theory or strengthening the Pentagon Fraud Theory. Practical implications, this study has significant implications for auditors, regulators, creditors and shareholders. The findings indicate that external pressure (leverage) and capability (change of directors) can be used to detect fraud in financial statements.